Validation Report: outcome stories for CIAT-CCAFS projects in Colombia during 2014 - Wilson-Grau, Ricardo (2014)
In November 2014, I engaged with five Colombian government staff to validate two Outcome Stories prepared by CIAT staff describing governmental changes that CIAT science had influenced. The first Story described how the Ministry of Agriculture and Rural Development (MADR)1 and the Ministry of Environment and Sustainable Development (MADS) prioritized mitigation actions for the agriculture and livestock sector. CIAT’s contribution was its scientific collaboration in 2013 and 2014 with the Colombian government to identify appropriate mitigation measures for the agricultural sector and establish the evidence base for the Colombian Low Emission Development Strategy (LEDS). The second Story described how the Colombian National Planning Department (DNP) developed detailed sector level adaptation plans in part as a result of CIAT researchers’ measurement of the economic impacts of climate change in the water, biodiversity and livestock sector. The purpose of the validation was to both verify and enrich the understanding of the influence of CIAT research in decision-making at the policy level.